Integrating Cognitive Science with Islamic Philosophy: Emergence and Current Challenges - Ahmad, Mudasir; Khan , Tariq Rafeeq (Universitas Islam Indonesia, 2024)
In this paper, an attempt has been made to discuss the inclusive approach of cognitive science with Islamic philosophy. Islamic philosophy has put forth a significant role in the development of cognitive science. The emergence of cognitive science in Islamic philosophy commences with the knowledge about heart, soul, ‘reasoning’, ‘aql’, cognition ‘marifat’ contemplation ‘fikr’ meditation ‘zikr’, mystic cognition, and their relation with the mental processes like ‘tafakur’, ‘tadabur’, ‘taakiloon’ and learn ‘iqra’. This paper tries to show the novel ideas of cognitive science with the new advances and researches in Neuro-theology, religious mantras and spiritual nexus. It also discusses the basic building blocks of cognitive sciences which are ilm (knowledge), mind, heart, soul, reasoning, language, intellect and mystic cognition. As the role of Islamic philosophers are significant in the emergence of cognitive science and there are various thinkers who led their contribution in cognitive science but I have included only some notable Islamic cognitive scientists in this paper. This paper also examines the future aspect of religious sciences in the growth of cognitive science.